One-third of vertiginous episodes during the follow-up period are caused by benign paroxysmal positional vertigo in patients with Meniere's disease. (November 2014) - Taura, Akiko; Funabiki, Kazuo; Ohgita, Hideaki; Ogino, Eriko; Torii, Hiroko; Matsunaga, Mami; Ito, Juichi
Abstract Conclusion: In the present study, about one-third of patients with Meniere's disease developed benign paroxysmal positional vertigo (BPPV)-like attacks. Additionally, more than one-third of all vertigo attacks were BPPV-like attacks. Thus, vertigo attacks in patients with Meniere's disease must be carefully treated because the therapy for such vertigo attacks is totally different from the therapy for BPPV. Objective: Physicians sometimes encounter patients with previously diagnosed Meniere's disease who develop BPPV attacks during the course of clinical follow-up. In this study, we explored the frequency with which BPPV was involved in all vertiginous episodes among patients with Meniere's disease. Methods: This retrospective study involved 296 patients with Meniere's disease who visited Kyoto University Hospital. The diagnosis of Meniere's disease was based on the guidelines for the diagnosis of Meniere's disease proposed by the Committee on Hearing and Equilibrium. We judged the cause of vertigo as one of the following five types: (1) definite Meniere's disease attack, (2) suspicious Meniere's disease attack, (3) definite BPPV attack, (4) suspicious BPPV attack, or (5) unknown. Results: In all, 96 patients (32.8%) developed BPPV-like attacks, and 187 vertiginous episodes (37.9%) were caused by BPPV. The lateral semicircular canal was the most frequently involved canal.